n+6=6*(2+3)

Simple and best practice solution for n+6=6*(2+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+6=6*(2+3) equation:


Simplifying
n + 6 = 6(2 + 3)

Reorder the terms:
6 + n = 6(2 + 3)

Combine like terms: 2 + 3 = 5
6 + n = 6(5)

Multiply 6 * 5
6 + n = 30

Solving
6 + n = 30

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + n = 30 + -6

Combine like terms: 6 + -6 = 0
0 + n = 30 + -6
n = 30 + -6

Combine like terms: 30 + -6 = 24
n = 24

Simplifying
n = 24

See similar equations:

| r+(-5)=-15 | | c=0.02Y^2+0.1Y+25 | | -9(4+2+3)= | | 4y(9y)=36y | | a^2x+3x=2a | | 3x-4x+2x=5 | | 7(2x-4)+6(X+3)=30 | | 3(q+4/3)=2 | | 8x^2+24x-11=0 | | -62=6x+4 | | x-.30=75 | | -(2x-20)=14 | | -28+7=x+46 | | 2x-5-3x+7=10 | | -10x+35=-3x+77 | | -132=-3(5m+4) | | 2(3x-3)=x-1 | | 5x^2+12x=-1 | | 98=7(x+6) | | 3x+50+4x+32= | | 4x+6(-3x+4)=122 | | 2x+2=3x+2+x-8 | | 31=9(2x-5) | | 9x-3y= | | 6x-7+2x+3= | | 23=1-6x+4 | | 7t^2+12t+1=0 | | 5x+6=7x-1 | | -6x-8(6-6x)=162 | | Y=200-6.5x | | 7x+9-6x=16 | | 5x+275=x(30) |

Equations solver categories